Persepsi dan Partisipasi Masyarakat Terhadap Penerapan Program Bank Sampah Pertiwi Lestari di Desa Penyaringan - Ni Ketut Ayu Widaningsih; Made Ary Meitriana (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
The purpose of this study was to identify (1) public perception reviewed from the dimension of perception performers, (2) public perception reviewed from the perceived object dimension (3) public perception reviewed from the context dimension of the perception situation, (4) community participation reviewed from the indicators of engagement results, and (5) community participation reviewed from special interest indicators to the implementation of the Pertiwi Lestari Waste Bank program in Penyaringan Village. The sample of this study was determined through purposive random sampling in total of 96 respondents. The data collection methods used were questionnaires, interviews, and documentation. Data analysis technique used was descriptive analysis. The results of this study show that (1) public perception reviewed from the dimension of perception performers obtains a score of 4311, in the range of scores of 4032-4800 and categorized as strongly agreed. (2) Public perception reviewed from the dimensions of the perceived object obtains a score of 856, being in the range of scores of 806-960 and categorized as strongly agreed. (3) Public perception reviewed from the context dimension of the situation obtains a score of 2532, in the range of scores 2420-2880 and categorized as strongly agreed. (4) Community participation reviewed from the indicator of engagement result obtains a score of 331, in the range of scores 288-384 and categorized as active. (5) Participation reviewed from special interest indicators obtains a score of 599, in the range of scores 576-768 and categorized as active.